Echocardiographic Assessment of Right Ventricular Function in COVID-19 Recovered Patients at a Tertiary Care Hospital - Balqees, Nayab; Hussain, Sajjad; Yusuf, Rizwan; Din, Mir Jalal Ud; Khalil, Hafsa; Ali, Jahanzab; Sana, Ayesha; Javaid, Rehana (Pakistan Armed Forces Medical Journal, 2022)
Objective: To detect residual RV dysfunction on a right ventricle focused Transthoracic Echocardiography (TTE) in COVID-19 infection survivors with lung involvement. Study Design: Analytical Cross sectional study design. Place and Duration of Study: Combined Military Hospital Abbottabad Pakistan, Feb 2022 to Apr 2022. Methodology: 87 patients who had suffered from and survived COVID-19 infection with definite involvement on CT scans of the chest were studied after discharge. Echocardiography was done to determine the RV anatomical and functional parameters to determine the relationship between extent of lung involvement and transthoracic echocardiographic parameters.Data was entered in Microsoft excel and exported to SPSS v 23 for analysis. Results: The initial sample size was of 87 patients. Due to suboptimal ECHO studies 7 cases were excluded. Males represented 62.5% (n=50) and females 37.5% (n=30). The ages ranged from 27 to 80 years, mean 53.08±12.77 years. Based on the CT severity score severe infections were 61.3 %(n=49) and mild 38.8% (n=31). The CTSS ranged from 6 to 30 with a mean of (17.74±7.13). In our study we found that on TTE, there was a statistically significant difference in 2 of the anatomical parameters; RVOT PLAX (RVOT diameter in Parasternal long axis view) [27.4 vs 28.3; p=0.02], RVOT-Dis (Distal RVOT dia) [22.8 vs 24; p=0.01]. In addition, there was a statistically significant difference in all the functional parameters of RV function TDI S vel (Systolic Tissue Doppler Velocity of the Tricuspid Annulus by Tissue doppler imaging) [7 vs4.9; p<0.0001], RIMPPW (Right Ventricular Index of Myocardial Performance by Pulse wave doppler) [0.46 vs0.38; p<0.0001], RIMP-TDI (Right Ventricular Index of Myocardial Performance by Tissue doppler imaging) [0.57 vs 0.48; p<0.0001]. RV-FAC (RV-Fractional Area Change) was statistically insignificant. [42.8% vs 43.2%; p=0.6]. Conclusion: Our study showed that in patients with definite lung involvement on chest CT scans, functional echocardiographic parameters of Right ventricular function were affected in line with the severity of lung involvement.